Trading institutions and price discovery: the cash and futures markets for crude oil - Albert Ballinger; Jr. Gerald P. Dwyer; Ann B. Gillette (Federal Reserve Bank of Atlanta, 2004)
We provide substantial evidence that the futures market for West Texas Intermediate crude oil increased the short-term volatility of the cash price of crude oil. We show that the variability of prices increased using both published posted prices and transaction prices for producers. This increased volatility in the price of crude oil may reflect information aggregated into the price, an increase the variance of shocks to the price of crude oil, or noise in the futures price that affects the cash price. We present evidence from experiments consistent with the interpretation that information aggregation not feasible in a posted-price market can explain at least part of the increase in variance. This evidence supports the proposition that information not previously aggregated into the cash price for crude oil is at least part of the reason for the greater variability of the cash price after the opening of the futures market and provides at least one example in which a futures market increased the volatility of the cash market, and prices became more efficient.
Keywords: 330; Ölmarkt; Rohstoffderivat; Marktmechanismus; Test